Evolutionary Conservation of Thyroid Hormone Receptor and Deiodinase Expression Dynamics in ovo in a Direct-Developing Frog, Eleutherodactylus coqui - Laslo, Mara; Denver, Robert J.; Hanken, James (Frontiers in Endocrinology, 2019)
Direct development is a reproductive mode in amphibians that has evolved independently from the ancestral biphasic life history in at least a dozen anuran lineages. Most direct-developing frogs, including the Puerto Rican coquí, Eleutherodactylus coqui, lack a free-living aquatic larva and instead hatch from terrestrial eggs as miniature adults. Their embryonic development includes the transient formation of many larval-specific features and the formation of adult-specific features that typically form postembryonically—during metamorphosis—in indirect-developing frogs. We found that pre-hatching developmental patterns of thyroid hormone receptors alpha (thra) and beta (thrb) and deiodinases type II (dio2) and type III (dio3) mRNAs in E. coqui limb and tail are conserved relative to those seen during metamorphosis in indirect-developing frogs. Additionally, thra, thrb, and dio2 mRNAs are expressed in the limb before formation of the embryonic thyroid gland. Liquid-chromatography mass-spectrometry revealed that maternally derived thyroid hormone is present throughout early embryogenesis, including stages of digit formation that occur prior to the increase in embryonically produced thyroid hormone. Eleutherodactylus coqui embryos take up much less 3,5,3’-triiodothyronine (T3) from the environment compared with X. tropicalis tadpoles. However, E. coqui tissue explants mount robust and direct gene expression responses to exogenous T3 similar to those seen in metamorphosing species. The presence of key components of the thyroid axis in the limb and the ability of limb tissue to respond to T3 suggest that thyroid hormone-mediated limb development may begin prior to thyroid gland formation. Thyroid hormone-dependent limb development and tail resorption characteristic of metamorphosis in indirect-developing anurans are evolutionarily conserved, but they occur instead in ovo in E. coqui.